Análisis de discurso sobre la representación y uso de la imagen del Gral. Eloy Alfaro Delgado en el gobierno de Alianza País. - Jiménez Reino, María de Lourdes (2014)
The paper presents an investigation into the use of the image and representation of General Eloy Alfaro Delgado in governing Alianza País, which will be studied through the analysis of speeches by Rafael Correa Delgado, chief representative of Alianza País during January 2012, the month in which celebrated 100 years of the death of Alfaro. The analysis was made from the considerations taken from the structuralist paradigm of communication, through semiotics theory, as a support of Critical Discourse Analysis. The methodology used although it is not incorporated as a formal method of study has been extracted from the assumptions provided by the Dutch theorist Teun A. Van Dijk, and follows a macro- analysis scheme, local meanings, formal structures of speech formats overall - local context analysis, taking into account also the categorical budgets set for the completion of the ideological analysis.